The Effect of Temperature on Thermochromic Leuco Dyes: A Meta-Analysis - Warsiki, Endang; Jayanegara, Anuraga; Juniati, Indira; Thamrin, Elfa Susanti; Nisrina, Aufa; Rardniyom, Chananpat (Green Engineering Society, 2024)
The effect of temperature treatment, either increasing or decreasing the temperature of leuco dyes, can produce thermochromic by looking at the changing color of samples resulting from experiments. The colors that are seen namely brightness (L), a* value, b* value, chroma, degree of hue (oHue), color difference ( E), and color density (CD). This research was conducted to analyze the temperature treatment of the thermochromic leuco dye against color characteristics resulting from meta-analysis using secondary data from pre-existing research. The total number of journals used was 21 studies and the data obtained were 82 sets of treatments. The data were then analyzed using IBM SPSS software, which used quadratic and linear regression models. The results of the study with a temperature range between -8°C to 95°C show that the effect of temperature treatment with an increase in temperature can cause a significant elevation impact on brightness values (p <0.002, R2 0.174), b* (P <0.01, R2 0.146), color difference ( E) (P <0.0012, R2 0.117), and ohue (P <0.053, R2 0.087). A significant reduction effect can be seen in the chroma value (P <0.007 R2 0.134) and the color density (P <0.007, R2 0.128). The impact of temperature treatment was not significant (p> 0.1) for a* value.